A retrospective cohort analysis of plasma TAT level trends and adverse pregnancy outcomes in early pregnancy patients with newly diagnosed VTE - Rong Zhang; Xiao Mei Wang; Chao Yun Jiang; Tian Hong Cai; Jian Feng He; Kai Chen; Dian Xi Chen; Teng Hui Zhan (Thrombosis Journal)
Abstract Objective Venous thromboembolism (VTE) is a leading cause of maternal mortality, yet effective biomarkers for early prediction of adverse pregnancy outcomes remain limited. We aimed to investigate the association between changes in thrombin-antithrombin complex (TAT) levels and adverse pregnancy outcomes in early-pregnancy patients with VTE. Methods In this retrospective cohort study, we enrolled 89 pregnant women diagnosed with VTE during early pregnancy (< 14 weeks) who received care at Fujian Maternity and Child Health Hospital between June 2021 and May 2024. Plasma TAT levels measured in early and mid-pregnancy were collected as exposure variables, while adverse pregnancy outcomes (including miscarriage, preterm birth, and fetal growth restriction) served as outcome variables. Multivariate regression analysis was performed to evaluate the association between TAT level changes and adverse pregnancy outcomes, adjusting for potential confounding factors including age, BMI, and obstetric history. Additionally, threshold effect analysis was conducted. Results After adjusting for potential confounding factors including age, BMI, and underlying conditions, changes in TAT levels were significantly associated with a reduced risk of adverse pregnancy outcomes (adjusted OR = 0.62, 95% CI: 0.47–0.80). Threshold effect analysis identified a critical turning point of -2.87 in TAT level changes (TATp2-1), below which the risk of adverse outcomes increased significantly (adjusted OR = 0.37, 95% CI: 0.22–0.63). Conclusion The association between TATp2-1 and adverse pregnancy outcomes in early pregnancy VTE patients was non-linear. A threshold effect was observed with an inflection point of -2.87. When the TATp2-1 were below − 2.87, there was a significantly increased risk of adverse pregnancy outcomes.